Usability Studies on the Web Page Design for E-Commerce - Lob Yussof, Rahmah (2000)
The potential of the World Wide Web on the Internet as a commercial medium and market bas been widely documented in a variety of media. E-commerce is a new phenomenon that changes the way people do business. Therefore, in this report the writer will explore the usability studies on the web page design for e-commerce. The first chapter is the introduction where overview of the project includes the problem statement, problem solving, objectives and scope of the project is discussed. The role and definition of WWW, E-Commerce and its history is discussed in chapter two. Further, in the same chapter the writer continues examine problems with the web page design (e--commerce) and factors affecting the decision to purchase. In the third chapter, the methodology of the web page design is spell out. In chapter four, security technology, which can pose significant threats to web page for e-commerce, is mentioned. Chapter five includes a comparison is done to find out web page design for e-commerce in Malaysia and other countries, and sample web page design based on the usability studies discussed in the above chapters is done. Finally findings and conclusion for this project is mentioned in chapter six.